Instrument of understanding level test of newtons law concept: case study flying fox ride in Bukik Chinangkiek Edupark, West Sumatera, Indonesia - Lisa, Tessa Destia Putri (Tanjong Malim, 2021)
Instrument of understanding level test of newtons law concept: case study flying fox ride in Bukik Chinangkiek Edupark, West Sumatera, Indonesia by Lisa, Tessa Destia Putri